Helicobacter pylori Infection in Gastroesophageal Reflux Disease in the Asian Countries - Su Jin Hong; Sang Woo Kim (Gastroenterology Research and Practice)
Helicobacter pylori infection, a common infection in many countries, is related to the clinical course of upper gastrointestinal diseases. Gastroesophageal reflux disease (GERD) is a common esophageal disease in Western countries and its prevalence is increasing in Asian countries. The pathophysiology of GERD is multifactorial. Although no single factor has been isolated as the cause of GERD, a negative association between the prevalence of H. pylori and the severity of GERD, including Barrett’s esophagus, has been demonstrated in epidemiological studies. The high prevalence of H. pylori infection affects the incidence of GERD in Asian countries. In the subjects with East Asian CagA-positive strains, acid injury may be minimized by hypochlorhydria from pangastritis and gastric atrophy. Additionally, host genetic factors may affect the development of GERD. The interactions between genetic factors and the virulence of H. pylori infection may be the reason for the low prevalence of GERD in Asian countries. H. pylori eradication is not considered pivotal in GERD exacerbation based on evidence from Western studies. A recent meta-analysis demonstrated that eradication therapy of H. pylori was related to a higher risk of developing de novo GERD in Asian studies. H. pylori infection remains an inconclusive and important issue in GERD in Asian countries.